Displacement of the South Pole from 2006 to 2021: Role of sea ice and Antarctic surface temperature - Pirti, Atinc; Yucel, Mehmet Ali; Hosbas, Ramazan Guersel (MASARYK UNIV PRESS, 2022)
The effect of global warming on the southern polar regions necessitates careful monitoring of glacier deformations and their movements, as well as an understanding of atmospheric physics. For this purpose, the yearly movements of UNAVCO stations-South Pole Station (AMU2) (winter-summer) and other stations in the South Pole region have been observed in this paper for about a fifteen-year period (2006-2021). In addition, the area differences of the Antarctic continent due to seasonal changes (winter-summer) between 1980 and 2021 were investigated in this study. Moreover, the height values of the stations on the Antarctic continent were observed seasonally. The subglacial lakes in the Antarctic continent cause the differences in the height values as a result of the seasonal changes. A decrease in sea ice of 0.91 million km(2) for the winter season and 0.55 million km(2) for the summer season during a 41-year period has been determined for four sectors of the Antarctic continent. The temperature changes on the Antarctic continent in the summer and winter seasons (2005-2022) were also evaluated in this paper. Air temperature increases was apparent especially in the Antarctic Peninsula, East Antarctic and West Antarctic coasts. The Weddell Sea and the Amundsen Sea regions have had the most sea ice loss, each with 1.24 million km(2). On the other hand, it can be observed that the East Antarctic sector has expanded by 0.32 million km(2).
Keywords: Antarctica; South Pole; GNSS; Satellite images; CLIMATE VARIABILITY; OCEAN CLIMATE; PLATE MOTION; DEFORMATION; STATION; LAND; Environmental Sciences & Ecology; Geology